Some Highly Potent Nepalese Medicinal Plants with Antimicrobial Properties - Khanal, Asmita; Shrestha, Sabina; Adhikari, Rameshwar (Current Pharmaceutical Design, 2024)
In recent years, microbial infections have emerged as a serious global health problem, necessitating the search for novel and effective treatments. Medicinal plants contain phytochemicals that can be used to prevent and treat various infections. Traditional medicinal practices have long relied on the healing properties of herbs, and Nepal is particularly rich in this knowledge. Bioactive compounds found in plants possess antibacterial, antifungal, and antiviral properties, making them a valuable resource for the fight against microbial infections. This review focuses on three medicinal plants native to Nepal, Amomum subulatum, Cymbopogon jwarancusa, and Cinnamomum glaucescens, which contain potent antimicrobial phytochemicals. The traditional uses, bioactive components, and biological activities of these plants are discussed, providing valuable insights into their potential as natural remedies to combat microbial infections.
Keywords: Amomum subulatum